DAMPAK LINGKUNGAN PEMBELAJARAN TERHADAP PRESTASI AKADEMIK MAHASISWA DI PERGURUAN TINGGI - Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the impact of learning atmosphere on students' academic achievement in higher education. Considered as a key factor, the learning environment has a great influence on the academic results achieved by students. Through observation and observation methods, this study aims to reveal the quality of learning facilities, teaching methods, and the overall academic atmosphere. The findings show that these three elements have a very significant impact on the achievement of academic achievement achieved by students. This research contributes to the understanding that good academic ability can be obtained from a supportive learning atmosphere and participation in various development and learning activities. However, a limitation of this study is the lack of detailed data on the semester level of students, which must be observed as material for further analysis of student achievement patterns over time. From the results of this study, it is recommended that efforts be made to always increase learning motivation, personal involvement, and increase student potential and creativity as a top priority in improving their academic achievement in the future.